NUMERICAL SOLUTION TO OPTIMAL CONTROL PROBLEMS USING COLLOCATION METHOD VIA PONTRYAGIN’S PRINCIPLE - Adamu, Samuel; Aduroja, O. O.; Bitrus, K. (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, Lucas polynomial approximate solution is considered to develop a collocation technique for solving optimal control problems with implementation in block using forward backward sweep method. The collocation block method developed is stable and convergent. The method is implemented using MATLAB code, and the examples show that forward-backward sweep methods with the collocation method is an efficient technique for solving optimal control problems as compared with some existing methods.
Keywords: Block method; Optimal control problem; Pontryagin's principle